2018
DOI: 10.3390/ijms19113635
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic Approach for Understanding the Mechanisms of Delayed Corneal Wound Healing in Diabetic Keratopathy Using Diabetic Model Rat

Abstract: Diabetes mellitus is a widespread metabolic disorder, and long-term hyperglycemia in diabetics leads to diabetic keratopathy. In the present study, we used a shotgun liquid chromatography/mass spectrometry-based global proteomic approach using the cornea of streptozotocin-induced diabetic (STZ) rats to examine the mechanisms of delayed corneal wound healing in diabetic keratopathy. Applying a label-free quantitation method based on spectral counting, we identified 188 proteins that showed expression changes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 72 publications
(85 reference statements)
2
15
0
Order By: Relevance
“…STZ injection was first reported to have diabetogenic properties in 1963 and has since become a chemical widely used to model diabetes in experiments. Briefly for this model, rats are given daily injections of 160–240 mg/kg STZ for 2 days in order to mimic type I diabetes 1 5. The onset of hyperglycemia is rapid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…STZ injection was first reported to have diabetogenic properties in 1963 and has since become a chemical widely used to model diabetes in experiments. Briefly for this model, rats are given daily injections of 160–240 mg/kg STZ for 2 days in order to mimic type I diabetes 1 5. The onset of hyperglycemia is rapid.…”
Section: Resultsmentioning
confidence: 99%
“…Yamamoto et al ’s study used shotgun liquid chromatography mass spectrometry to detect differentially expressed proteins in the cornea of STZ rats compared with controls 1. The study identified 188 proteins that were expressed at least twofold higher in STZ rats compared with controls and were serving as candidate proteins in the pathogenesis of delayed wound healing in diabetes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a C-terminal product of lumican, which can be generated for example by MT1-MMP cleavage ( Figure 5 ), has been shown to bind to ALK5 and promote corneal epithelial wound healing, increasing both epithelial cell migration and proliferation ( Yamanaka et al, 2013 ; Gesteira et al, 2017 ). Although lumican expression is important during the process of wound healing, persistent up-regulation of lumican beyond wound closure can lead to reduced adhesion of corneal epithelial basal cells, as seen in streptozotocin-induced diabetic rats ( Yamamoto et al, 2018 ).…”
Section: Keratan Sulfate Proteoglycans (Kspgs)mentioning
confidence: 99%
“…We previously used this methodology to evaluate changes in protein expression in the lens and cornea of STZ rats and found decreased superoxide dismutase. This decrease contributed to the progression of diabetic cataracts and overexpression of lumican, leading to delayed corneal wound healing in diabetic keratopathy-affected corneas (11,12).…”
Section: Introductionmentioning
confidence: 99%